Microemulsified Gel Formulations for Topical Delivery of Clotrimazole Structural and In Vitro Evaluation - Yasir Siddique, Muhammad (Langmuir : the ACS journal of surfaces and colloids, 2021)
Microemulsified gels (μEGs) with fascinating functions have become indispensable as topical drug delivery systems due to their structural flexibility, high stability, and facile manufacturing process. Topical administration is an attractive alternative to traditional methods because of advantages such as noninvasive administration, bypassing first-pass metabolism, and improving patient compliance. In this article, we report on the new formulations of microemulsion-based gels suitable for topical pharmaceutical applications using biocompatible and ecological ingredients. For this, two biocompatible μE formulations comprising clove oil/Brij-35/water/ethanol (formulation A) and clove oil/Brij-35/water/1-propanol (formulation B) were developed to encapsulate and improve the load of an antimycotic drug, Clotrimazole (CTZ), and further gelatinized to control the release of CTZ through skin barriers. By delimiting the pseudo-ternary phase diagram, optimum μE formulations with clove oil (∼15%) and Brij-35 (∼30%) were developed, keeping constant surfactant/co-surfactant ratio (1:1), to upheld 2.0 wt % CTZ. The as-developed formulations were further converted into smart gels by adding 2.0 wt % carboxymethyl cellulose (CMC) as a cross-linker to adhere to the controlled release of CTZ through complex skin barriers. Electron micrographs show a fine, monodispersed collection of CTZ-μE nanodroplets (∼60 nm), which did not coalesce even after gelation, forming spherical CTZ-μEG (∼90 nm). However, the maturity of CTZ nanodroplets observed by dynamic light scattering suggests the affinity of CTZ for the nonpolar microenvironment, which was further supported by the peak-to-peak correlation of Fourier transform infrared (FTIR) analysis and fluorescence measurement. In addition, HPLC analysis showed that the in vitro permeation release of CTZ-μEG from rabbit skin in the ethanolic phosphate buffer (pH = 7.4) was significantly increased by >98% within 6.0 h. This indicates the sustained release of CTZ in μEBG and the improvement in transdermal therapeutic efficacy of CTZ over its traditional topical formulations